Risk Of Preterm Birth Associated With Placenta Previa or Low-Lying Placenta and Preventive Measures: A Comprehensive Systematic Review - Sianipar, Imelda M.G; Juliana, Mutia (The Indonesian Journal of General Medicine, 2024)
Background: Women with placenta previa or a low-lying placenta face a heightened risk of both maternal and fetal complications during pregnancy. The aim of this study is to evaluate the risk of preterm birth at different gestational ages in women with placenta previa and low-lying placentas and its preventive measures. Methods: The review adhered to PRISMA 2020 standards and analyzed full-text English literature from 2014 to 2024. It excluded editorials, review papers from the same journal, and submissions lacking a DOI. Literature sources included PubMed, SagePub, SpringerLink, and Google Scholar. Result: A total of  500 articles were retrieved from online databases (PubMed, SagePub, SpringerLink and Google Scholar). After three rounds of screening, five articles directly relevant to the systematic review were selected for full-text reading and analysis. Conclusion: Placenta previa and low-lying placenta reveals significant risks of preterm birth, necessitating comprehensive strategies for prevention and management. Key preventive measures include early detection through routine ultrasound screening, careful management of high-risk pregnancies, and timely interventions such as elective cesarean section.